Design of Market Waste Biodigester as an Effort to Produce Renewable Energy for Climate Change Mitigation Strategy - Ulhasanah, Nova; Sarwono, Ariyanti; Salsabila, Thalita Kaltsum; Bakara, Putri Pitra Uli; Saputra, Wisnu; Kembaren, Adewita Br (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2024)
The mismanagement of solid waste transportation to landfills contributes to various environmental issues, including increased greenhouse gas (GHG) emissions, propagation of disease vectors, aesthetic degradation, and interference with market activities. Addressing these challenges necessitates efficient waste processing at the source to mitigate waste accumulation at temporary dump sites and reduce GHG emissions. This study proposes the design of an integrated anaerobic digester at Pasar Kemiri Muka, specifically selected for its ability to convert organic waste into renewable energy. The anaerobic process is advantageous as it produces methane with a high calorific value, suitable for generating electricity. The generated electricity is then utilized to improve street lighting in the market area, which currently suffers from insufficient and poor-quality lighting. The proposed system is designed to power 14 LED street lights, requiring only 10m² for installation and incurring an operational cost of IDR 525,000. This approach not only provides a sustainable energy source but also enhances local infrastructure, contributing to a cleaner and more efficient market environment.